PROTOTYPE PERANCANGAN MEMBUKA DAN MENUTUP PINTU GERBANG RUMAH MENGGUNAKAN MOTOR DC BERBASIS ANDROID - Irwanto Irwanto; Vaka Gustiono (Indonesian Journal of Business Intelligence (IJUBI), 2019)
The gate is one of the main security in maintaining a home. Because the gate is the first coating to protect the contents and building of the house. It also did not escape the perpetrators of robbery criminal acts to have a way to overcome the weakness of protection given extra security on the fence. With the development of wireless technology, one of which is cheap and easy-to-use Bluetooth that can be reached by mobile phones that can be reached by all groups, Bluetooth is a facility on cellular telephones that is used to order to open and close doors with a Bluetooth application that is installed on a smartphone. The testing tool system method opens the gate of the house using an Android-based DC motor using an ATMEGA 8 microcontroller consisting of several blocks that are interconnected to one another. The results of the whole set of tools open and close the automatic gate using an android-based motor from a minimum system of ATMEGA 8, 5V Power Supply, blue-tooth, relay, handphone, LCD. Each component is interrelated and connected to form a whole set of tools opening and closing automatic gates using an Android hard-ware based hard-ware. Based on the experimental results the following conclusions can be drawn: (1) Bluetooth can work with a speed of 2.4 GHz and within 10 meters, (2) The speed of the blue-tooth application on the device is 0.1 s and (3) Relay is used as much as 4 to control 4 commands i.e. the first door is open and closed and the second door is open and closed.